New combinations in Orchidaceae of Mexico - Solano, Rodolfo; Salazar, Gerardo A.; Jiménez, Rolando (Instituto de Ecología, A.C., 2011)
New combinations are proposed here for 26 species and one variety belonging to 13 genera of Mexican Orchidaceae. These combinations are required to comply with current taxonomic concepts and ongoing revisionary treatment of the orchids of Mexico. The collector and number of the type specimen for the recently described Acianthera sotoana are corrected.